Bioremoval of Co(II) by a novel halotolerant microalgae Dunaliella sp. FACHB-558 from saltwater - Liu, Chenglong; Wen, Xueer; Pan, Huiqiao; Luo, Ying; Zhou, Junyang; Wu, Yuzhe; Zeng, Zhiyong; Sun, Ting; Chen, Jun; Hu, Zhangli; Lou, Sulin; Li, Hui (Frontiers in Microbiology, 2024)
Cobalt pollution is harmful fordamaging aquatic ecosystems and even endangering human health. As the primary producer of aquatic ecosystems in hypersaline environments, unicellular planktonic Dunaliella microalgae is considered to be a low-energy and, eco-friendly biosorbent that removes excess cobalt and enhances the vitality of coastal and marine ecosystems. In this study, we found that thea halotolerant microalgae named Dunaliella sp. FACHB-558 could grow under in the salinity condition range with of 0.5-4.5 M NaCl. Phylogenetic analysis based on rbcL-gene sequences revealed Dunaliella sp. FACHB-558 was is a close relative of Dunaliella primolecta TS-3. At lab-scale culture, Dunaliella sp. FACHB-558 exhibited high tolerance to heavy metal stressess such cobalt, nickel, and cadmium. Treatment with 60 μM cobalt delayed the timepoint reaching the its stationary phase, but could achieve higher population density cultures in long-term cultivation. Furthermore, Decreased concentration of cobalt ions in the liquid medium reflected Dunaliella sp. FACHB-558 had has the ability to adsorb the cobalt ions in aquatic environment, which was evidenced by the decreased amount of cobalt in the culture medium. Besides, the tolerance of Dunaliella sp. FACHB-558 to cobalt stress was correlated with enhanced nitric oxide content and peroxidase activity. Autophagy inhibitor 3-MA enhanced nitric oxide burst, increased peroxidase activity and accelerated the bioremoval of cobalt by Dunaliella sp. FACHB-558, suggesting autophagy pathway played a negative role in responses of Dunaliella microalgae to cobalt stress in Dunaliella sp. FACHB-558. In summary, our study identified a novel microalgae possessing high cobalt tolerance and provided a promising natural biosorbent for the research and application of heavy metal bioremediation technology.Unlike organic pollutants, heavy metals cannot be decomposed and can be gradually enriched in organisms through the food chain and finally, and accumulated in the human body after continuous enrichment [1]. Cobalt is an essential micronutrient for humans, animals, crops and algae [2]. However, excessive cobalt from sewage irrigation, sludge application, pesticides and fertilizers enter farmland,